1-(2-Allylaryl)-1H-pyrroles as Building Blocks for Novel 4-Methyl-4,5-dihydropyrrolo[1,2-a]quinoline Derivatives - Orejarena, Julio Cesar; Gómez, Sandra Liliana; Palma, Alirio; Cobo, Justo; Nogueras, Manuel (Synlett, 2014)
Novel substituted 4-methyl-4,5-dihydropyrrolo[1,2-a]-quinolines were prepared by a simple two-step approach involving a Clauson-Kaas reaction of a substituted ortho-allylaniline followed by acid-catalyzed regioselective intramolecular Friedel–Crafts alkylation of the resulting 1-(2-allylaryl)-1H-pyrroles. All the synthetized compounds were fully characterized by IR, 1H and 13C NMR spectroscopy, and mass spectrometry.
Keywords: pyrroles; quinolines; alkylation; heterocycles; cyclization